Analysis of Digital Media Literacy Skills For Students of UIN Syarif Hidayatullah Jakarta - Nahdatul Zahra; Dinda Regina Rahman; Wahyunengsih Wahyunengsih (KONTEKSTUAL : Jurnal Ilmu Komunikasi, 2022)
The learning process since mid-2020 has changed from face-to-face learning in general, to online learning. Because at that time Indonesia was entered with the Covid-19 virus. Adaptation to the digital world has to be done to facilitate the online learning process, therefore the purpose of this research is to analyze the digital media literacy skills of UIN Syarif Hidayatullah Jakarta students, especially students of the Journalism Study Program, Faculty of Da'wah and Communication Studies. This study uses a quantitative descriptive approach and data collection through a questionnaire in the form of Google Forms. In the questionnaire, there are several statements about the four components of digital media literacy ability. Based on the results of the study, it can be concluded that the ability of Journalistic Students at UIN Syarif Hidayatullah Jakarta is in the Very Good category. AbstrakProses pembelajaran sejak pertengahan tahun 2020 lalu berubah dari pembelajaran tatap muka seperti pada umumnya kini menjadi pembelajaran daring atau secara online. Karena saat itu Indonesia dimasuki dengan virus Covid-19. Adaptasi terhadap dunia digital sudah harus dilakukan untuk mempermudah proses pembelajaran daring (online), oleh karena itu tujuan penelitian ini adalah menganalisis kemampuan literasi media digital pada mahasiswa UIN Syarif Hidayatullah Jakarta, khususnya Mahasiswa Progran Studi Jurnalistik, Fakultas Dakwah dan Ilmu Komunikasi. Penelitianini menggunakan pendekatan deskriptif kuantitatif dan pengambilan data melalui kuesioner berupa google form. Dalam kuesioner terdapat beberapa pernyataan dari empat komponen kemampuan literasi media digital. Berdasarkan dari hasil penelitian dapat disimpulkan bahwa kemampuan mahasiswa jurnalistik UIN Syarif Hidayatullah Jakarta berada dalam kategori sangat baik.